Impact of Social Restrictions on ISPA Dynamics in Tasikmalaya City (2018-2023): A Counterfactual SIRS Model Analysis - Anggi Jelita Sitepu; Putri Nabawy; M Hasan Wijaya (Journal of Information Technology and Computer System, 2026)
The COVID-19 pandemic and the implementation of Non-Pharmaceutical Interventions (NPIs), such as Large-Scale Social Restrictions (PSBB), have drastically altered the transmission landscape of endemic respiratory diseases. This study aims to quantitatively evaluate the impact of social restrictions on the incidence of Acute Respiratory Infection (ISPA) in Tasikmalaya City and to elucidate the mechanisms driving the post-pandemic case resurgence. A dynamic SIRS (Susceptible-Infected-Recovered-Susceptible) mathematical model was constructed and calibrated using historical time-series data from 2018 to 2023, incorporating the biological factor of waning immunity. To measure policy effectiveness, a counterfactual analysis was performed by comparing the factual simulation (with interventions) against a hypothetical no-intervention scenario. The results demonstrate that the model achieved a high goodness-of-fit, accurately replicating the sharp decline in cases during the 2020-2021 restriction period and the significant "rebound" to pre-pandemic levels in 2023. The counterfactual analysis estimates that social restrictions prevented approximately 50,000 to 60,000 potential ISPA cases cumulatively over the two-year period. The study concludes that while NPIs were highly effective in suppressing transmission, the subsequent resurgence was a predictable mathematical consequence of "immunity debt" the accumulation of susceptible individuals due to prolonged lack of pathogen exposure. These findings underscore the necessity for anticipatory surveillance and targeted interventions during the transition from pandemic to endemic phases.